Characterization of Yellow Bourbon coffee strains for the production of differentiated specialty coffees - Romano, Lucicleia Souza [UNESP]; Giomo, Gerson Silva; Coelho, Anderson Prates [UNESP]; Filla, Vinicius Augusto [UNESP]; Lemos, Leandro Borges [UNESP] (My University, 2022)
The demand for specialty coffees in the national and international market grows and generates an excellent opportunity for the exploration of new business. The cup quality of coffee is defined by the genetic predisposition of varietal groups, effects of the production environment, crop management, and form of post-harvest processing. Genotypes of Yellow Bourbon have already shown a predisposition to the production of excellent cup quality, but it may differ in sensory attributes and cup quality. The aim of this article was to evaluate the agronomic and qualitative performance of Yellow Bourbon strains from the Active Germplasm Bank of the Agronomic Institute of Campinas, in order to identify the best genotypes for the production of specialty coffees. The experiment was conducted in São Sebastião da Grama, SP, Brazil, at 1,100 meters of altitude in a medium-textured Ultisol. Treatments consisted of 14 strains of Yellow Bourbon, arranged in a randomized block design with three replicates. Field, post-harvest and laboratory evaluations were carried out. The strains IAC J3-1, IAC J9-16 and IAC J19-18-10 stood out in terms of yield values and sensory quality above the average of the studied group. The strains IAC J9-16 and IAC J19-18-10 showed predominance of floral and honey nuances, respectively, indicating that they may have high potential to express these characteristics in the beverage. The results suggested that there are Yellow Bourbon strains suitable for production and with superior cup quality, which highlights the importance of the appropriate choice of genotypes for the production of differentiated specialty coffees.
Keywords: beverage sensory profile; Coffea arabica L; genotypes; lineages; yield